Tree species diversity in tropical rainforest of Okomu forest reserve, Nigeria (Agriculture, Food, and Natural Resources Journal, 2024)
Nigeria's rainforests are characterised by enormous plant diversity, intricate stand structures, and are potential biodiversity hotspots. Tree species in Nigeria's rainforest, which are essential to life and our environment are vanishing at a disturbing rate. Climate change impacts additionally exacerbate the plights of many indigenous tree species, as it may limit the capability of forest trees to speedily acclimatise. This study focused on the assessment of tree species diversity in Okomu Forest Reserve (OFR). Using a systematic sampling technique, sixty plots of 50 m × 50 m were alternately laid at 200 m intervals on 15 transects (one kilometer each). On each plot, trees with Diameter at Breast Height (DBH, cm) ≥ 10 were identified to species level and enumerated. The stand density (N/ha) was estimated. Based on abundance, species diversities were computed using the Importance Value Index (IVI, %), Shannon-Wiener diversity (H'), Simpson Dominance (D), and Evenness (E) indices. Data were analysed using descriptive statistics and alpha diversity analysis. Eighty-seven tree species belonging to 33 families were identified. The number of stem/ha ranged from 128.0 to 424.0. Trichilia monadelpha had the highest IVI (14.29), while Lannea welwitschii had the least (0.15). High H' (4.05), D (0.98), and E (0.91) were observed. This study has shown that OFR is better stocked in comparison with other tropical rainforests in Nigeria in terms of species distribution, especially those of the southern part of the country, Nigeria. This study therefore recommends that inventory of OFR should be regularly conducted at least every five years.
Keywords: Climate change; Importance value index; Natural forest; Tree diversity